2022
DOI: 10.3390/ijms23137159
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Targeting of Ovarian Cancer Stem Cells Using Estrogen Receptor Beta Agonist

Abstract: Ovarian cancer (OCa) is the deadliest gynecologic cancer. Emerging studies suggest ovarian cancer stem cells (OCSCs) contribute to chemotherapy resistance and tumor relapse. Recent studies demonstrated estrogen receptor beta (ERβ) exerts tumor suppressor functions in OCa. However, the status of ERβ expression in OCSCs and the therapeutic utility of the ERβ agonist LY500307 for targeting OCSCs remain unknown. OCSCs were enriched from ES2, OV90, SKOV3, OVSAHO, and A2780 cells using ALDEFLUOR kit. RT-qPCR results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…It was first reported that CCDC170 copy number variation can reduce its expression, thereby affecting the overall survival of patients with ovarian cancer, and it is a pathogenic mutation of ovarian cancer. At present, agonists such as luteinizing hormone releasing hormone, gonadotropin-releasing hormone and natural estrogen receptor β have shown beneficial effects on the treatment of ovarian cancer [57][58][59]. As a newly discovered downregulated molecular target of ovarian cancer, CCDC170 can provide a new direction for the development of agonists to reverse the treatment of ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It was first reported that CCDC170 copy number variation can reduce its expression, thereby affecting the overall survival of patients with ovarian cancer, and it is a pathogenic mutation of ovarian cancer. At present, agonists such as luteinizing hormone releasing hormone, gonadotropin-releasing hormone and natural estrogen receptor β have shown beneficial effects on the treatment of ovarian cancer [57][58][59]. As a newly discovered downregulated molecular target of ovarian cancer, CCDC170 can provide a new direction for the development of agonists to reverse the treatment of ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to IBC, ERβ was also found to be enriched in ovarian cancer stem cells (OVSC), and treatment with LY500307 reduced their stemness and induced apoptosis [114]. Treatment with LY500307 also significantly impaired the tumor-initiating potential of OVSCs in orthotopically implanted xenograft models [114]. Similarly, glioblastomas (GBM) express ERβ, and treatment of GBM cells with this selective agonist reduced proliferation and enhanced apoptosis in vitro (Figure 4C).…”
Section: Ly500307mentioning
confidence: 99%
“…Beyond TNBC, activating tumor-endogenous ERβ by treating mice bearing orthotopically implanted inflammatory breast cancer tumors with LY500307 led to reduced lung metastasis (Figure 4B) [65]. In addition to IBC, ERβ was also found to be enriched in ovarian cancer stem cells (OVSC), and treatment with LY500307 reduced their stemness and induced apoptosis [114]. Treatment with LY500307 also significantly impaired the tumor-initiating potential of OVSCs in orthotopically implanted xenograft models [114].…”
Section: Ly500307mentioning
confidence: 99%
“…ERβ forms homodimers or heterodimers with ERα. The receptor has tumor-suppressive and antiproliferative properties that compete with the functions of ERα in the reproductive system [ 34 ].…”
Section: Signaling Pathways Of Membrane Ers Vs Nuclear Ersmentioning
confidence: 99%